Influence of temperature, pressure, and oxygen fugacity on the electrical conductivity of dry eclogite, and geophysical implications. (24th June 2016) - Dai, Lidong; Hu, Haiying; Li, Heping; Wu, Lei; Hui, Keshi; Jiang, Jianjun; Sun, Wenqing
Abstract: The electrical conductivity of eclogite was measured at temperatures of 873–1173 K and pressures of 1.0–3.0 GPa within a frequency range of 0.1–10 6 Hz using a YJ‐3000t multianvil press and Solartron‐1260 impedance/gain‐phase analyzer. Three solid‐state oxygen buffers (Cu + CuO, Ni + NiO, and Mo + MoO2 ) were employed to control the oxygen fugacity. Experimental results indicate that the electrical conductivity of the samples tended to increase with increasing temperature, conforming to an Arrhenius relation. Under the control of a Cu + CuO oxygen buffer, the electrical conductivity of the eclogite decreased with a rise in pressure, and its corresponding activation volume and activation energy at atmospheric pressure were calculated as −2.51 ± 0.29 cm 3 /mole and 0.86 ± 0.12 eV, respectively. At 2.0 GPa, the electrical conductivity of the eclogite increased with increasing oxygen fugacity, and the preexponential factor increased while the activation enthalpy decreased. The observed positive exponential factor for the dependence of electrical conductivity on oxygen fugacity, as well as the negative activation volume, confirm that the hopping of small polarons is the dominant conduction mechanism in eclogite at high temperatures and pressures. Our results suggest that the electrical conductivity of dry eclogite under various redox conditions cannot explain the high anomalies in conductivity under stable midlower continental crust and under the Dabie‐Sulu ultrahigh‐pressure metamorphic belt of eastern China. Key Points: Electrical conductivity of eclogite decreased with increasing pressure, and the activation volume and activation energy were calculated Electrical conductivity of eclogite increased with oxygen fugacity, and the hopping of small polarons is the dominant conduction mechanism The results for various redox conditions cannot explain the high anomalies in conductivity under Dabie‐Sulu UHPM belt of eastern China